RESEARCH ON CARBON STORAGE CAPABILITY OF SEAGRASS THROUGH BIOMASS (IN THE CASE OF THI NAI LAGOON, BINH DINH PROVINCE) - Luong, Cao Van; Nga, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2017)
Seagrass bed is one of important coastal ecosystems. Recently, it was reduced rapidly. This study provides more basic information on functions of seagrass in environment and ecology in the lagoon through the study on biomass to estimate carbon storage of seagrass. This research also provides scientific basic for development, expansion of seagrass beds and preparation to participate in the carbon market. Seagrass absorbs CO2, which protects environment and reduces effect of climate change. Research results showed that there were 7 species in Thi Nai lagoon, which were distributed over a total area of ​​180 ha with the average density and biomass of 1,649 ± 428 shoots/m2 and 125.68 ± 23.40 g.dry/m2 respectively. The organic carbon content in seagrass averaged 34.30 ± 1.82%. In Thi Nai lagoon, the total amount of organic carbon and carbon dioxide stored by seagrass was estimated at 136.7 tons and 501 tons respectively, corresponding to 24,583.